A Techno-economic and pricing strategy simulation model of multiple manufacturing companies supplying micro milling - Dirkse-van Schalkwyk, Theunis Gysbert (Stellenbosch : Stellenbosch University, 2017)
Thesis (DEng)--Stellenbosch University, 2017.